Teknik Problem Solving Dalam Meningkatkan Self-Control Warga Binaan Kasus Penganiayaan Anak Dilapas Kelas II A Banyuwangi - Huda, Sri Nurul; Yohandi; Sulaiman, A. Husam (CV. SINAR HOWUHOWU, 2025)
This study aims to describe the implementation of problem-solving techniques as an effort to enhance self-control among inmates convicted of child abuse at class IIA Banyuwangi Correctional Facility. The research employed a qualitative method with a case study design, involving a single inmate, M. I , as the subject. Data were collected through in-depth interviews, direct observation, and document review. The findings indicate that the application of problem-solving techniques assists the subject in identifying emotional triggers, understanding the problems encountered, and selecting more adaptive solution alternatives. Improvements in self-control were also influenced by the subject’s engagement in productive activities, such as working in the laundry section, which provided routine and income, as well as increased discipline in performing prayers. Overall, the problem-solving technique proved effective in strengthening self-control among inmates with a history of violent behavior.